A política nacional de humanização na produção de inflexões no modelo hegemônico de cuidar e gerir no SUS: habitar um paradoxo - Martins, Catia Paranhos [UNESP] (2015)
The National Humanization Policy - HumanizaSUS (NHP) was created in 2003 as from the recognition of innovative experiences of a SUS that works out and since then has been promoting changes in its attention and management. In this cartography, we have been interested in meetings, stories, everyday work situations, as well as in the feelings of strangeness, doubts and clashes that have been produced throughout our trajectory in HumanizaSUS. Many narratives have been linked in order to enable us to report fragments of this story. Official documents, notes from meetings, countless rounds of conversations through the experience of being a consultant at Ministry of Health were added to the 78 final documents/narratives of a course at NHP in the Midwest of Brazil, and also to the dialog with 5 other consultants. We have used authors of the Philosophy of Difference and also of Public Health, mainly the ones aligned with HumanizaSUS, who have helped us discerning the clues of capture and resistance, without feeling sorry for the present days. We have built two scooping plans that are connected and mutually dialog. In chapter 2, NHP and its remarkable moments, happenings and divergences were extensively covered. HumanizaSUS was discussed as an unfinished piece of work and collective duty and has been struggling for a place in the Ministry of Health in everyday services and academic production. In chapter 3, some challenges and obstacles for making health a right were discussed. The captures of contemporary history, SUS as a battle field, the several and unequal realities that exist in Brazil and the struggle for citizenship contribute to broaden the comprehension of how important HumanizaSUS proposal is. In the supporters' narratives we can see headways and retrocessions of SUS, a powerful movement that results from reformist battles regarding health care, but that also combats the hegemonic patterns...